2016
DOI: 10.1016/j.cognition.2015.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Comprehension priming as rational expectation for repetition: Evidence from syntactic processing

Abstract: Why do comprehenders process repeated stimuli more rapidly than novel stimuli? We consider an adaptive explanation for why such facilitation may be beneficial: priming is a consequence of expectation for repetition due to rational adaptation to the environment. If occurrences of a stimulus cluster in time, given one occurrence it is rational to expect a second occurrence closely following. Leveraging such knowledge may be particularly useful in online processing of language, where pervasive clustering may help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
47
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 60 publications
8
47
2
1
Order By: Relevance
“…In all three experiments, we find that speakers are more likely to produce a construction if they have just recently produced that construction themselves. The evidence for self-priming presented here is consistent with a number of corpus studies with similar findings (e.g., Gries, 2005;Jaeger & Snider, 2013;Mysl ın & Levy, 2016;Reitter et al, 2011). The current study is novel in that we see evidence for self-priming while ruling out alternative explanations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In all three experiments, we find that speakers are more likely to produce a construction if they have just recently produced that construction themselves. The evidence for self-priming presented here is consistent with a number of corpus studies with similar findings (e.g., Gries, 2005;Jaeger & Snider, 2013;Mysl ın & Levy, 2016;Reitter et al, 2011). The current study is novel in that we see evidence for self-priming while ruling out alternative explanations.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to this, we hope to determine whether the syntactic choices of one production trial directly influence the syntactic choices of subsequent trials. While a number of studies have shown that speakers tend to repeat themselves, potentially due to self‐priming or residual activation (e.g., Myslín & Levy, ; Reitter & Moore, ), these effects could result from confounds such as discourse factors favoring one structure over another, or a speaker's baseline preference for a construction, as we mention above. In order to determine whether there are dependencies between trials in the likelihood of selecting one structure over another, we apply a novel mixed effects autocorrelation analysis with a multinomial outcome to the current data set.…”
Section: Introductionmentioning
confidence: 97%
“…Chang, Dell, and Bock (2006) explain syntactic repetition as a kind of learning effect -that the original experience of hearing a type of event meaning expressed with a particular structure strengthens the connection between that event meaning and that Page 18 structure, leading speakers to be more likely to use that structure again in the future. Jaeger and Snider (2013) attribute syntactic priming to learning with the goal to reduce "joint effort" of interlocutors and to "minimize the expected future prediction error" (for related discussion of the effects of repetition on prediction errors experienced during comprehension, see Fine & Jaeger, 2013Fine et al, 2013;Myslin & Levy, 2016).…”
Section: Feedforward Audience Designmentioning
confidence: 99%
“…As a starting point for this investigation, we consider adaptation in other linguistic domains. Apart from the work on quantifiers, linguistic adaptation has been observed in phonetics (Babel, 2012;Clayards, Tanenhaus, Aslin, & Jacobs, 2008;Goldinger, 1998;Kleinschmidt & Jaeger, 2015;Kraljic & Samuel, 2005Norris et al, 2003), syntax (Fine & Jaeger, 2016;Fine, Jaeger, Farmer, & Qian, 2013;Kamide, 2012;Kroczek & Gunter, 2017;Myslín & Levy, 2016), 1 intonation and prosody (Kurumada, Brown, & Tanenhaus, 2012;Roettger & Franke, 2019), and with phenomena such as referring expressions (Brennan & Clark, 1996;Brennan & Hanna, 2009;Brown-Schmidt, 2009;H. H. Clark & Wilkes-Gibbs, 1986;Hawkins, Frank, & Goodman, 2017;Horton & Gerrig, 2005;Metzing & Brennan, 2003), contrastive inferences (Grodner & Sedivy, 2011;Pogue, Kurumada, & Tanenhaus, 2016), and lexical associations (Delaney-Busch, Morgan, Lau, & Kuperberg, 2019).…”
mentioning
confidence: 99%